Children and art in the "Beauty Children, Mirò and Contemporary Art" experience - Clara Silva (Firenze University Press, 2015)
Pedagogy has shown as children's first drawings, pictures and graphic expressions are not simply scribbles: on the contrary, they are real, meaningful outlines of a story. In order to enhance the meaning of children's drawings, the 'workshop' pedagogic-didactic model seems to be the most suited for a similar approach to aesthetic education. In light of these theoretical and methodological premises, this essay illustrates the project experiences carried out in numerous crèches and nursery schools both in Tuscany and some European countries, using Contemporary Art to enhance children's creativity. The project activities involved the children's whole sensorial sphere, together with their emotional experiences, arousing curiosity and promoting children's individuality and harmonic development as well.